Особливості розробки та публікації мобільних застосунків у App Gallery - Афанасьєва, А. М. (ХНУРЕ, 2021)
The termination of cooperation between Google and Huawei has led to the fact that Huawei on its new devices can no longer use Google services (app store, geolocation, maps, push notifications, analytics, etc.), which turns the device into a brick for the user. If it were not for a Chinese company, then, most likely, its business related to Android would have simply stopped there. However, the company is Chinese, big and they took the path of import substitution, quickly implementing functionality similar to Google services. This publication provides an overview of the development features for App gallery.
Keywords: App Gallery; Application; Developing